Insights into Hittite history and archaeology - Genz, Hermann; Mielke, Dirk Paul (Colloquia antiqua, 2011)
Summary: Hitherto, research on the Hittites has been highly specialised and often separated by discipline: history, philology and archaeology (in which natural sciences are taking a more prominent role). Unfortunately, no up-to date publication has been available to bring the work and evidence of these different fields together, making it extremely difficult for the non-specialist to obtain a general overview of Hittite studies. This volume closes that gap by providing contributions on several key issues in Hittite studies based on new developments and approaches from historical, philological and archaeological points of view. The subjects discussed include history, state and society, the written legacy, the environment and economy, foreign contacts, cities, temples and sanctuaries, military and warfare, pottery, and metals and metallurgy